The impact of Covid-19 On Micro Small Medium Enterprises (UMKM) in Tanjung Morawa Deli Serdang North Sumatera - Nainggolan*, Lya Novaria; Lubis, Irsad; Tanjung, Ahmad Albar; Sukardi, Sukardi; Ruslan, Dede (Universitas Syiah Kuala, 2023)
The Covid-19 virus is a deadly virus that is faced by almost all countries, without exception, in various parts of Indonesia. Our country Indonesia has been greatly affected by the spread of Covid-19. Various kinds of new variants are coming back, namely the Covid-19 variant of Delta, which forces the government to act quickly even though sometimes it's not right. All forms of policies are taken to suppress the spread of the virus. We call it Lock Down, Large-Scale Social Restrictions (PSBB), Micro-Scale Social Restrictions, there is also the Enforcement of Restrictions on Community Activities (PPKM in all provinces and DKI). Apart from health and mortality rates, Covid-19 does not also affect the economy. The middle to lower class society is greatly affected by this condition. Therefore, this research will review the impact of COVID-19 on the economic conditions of UMKM in the Tanjung Morawa area, Deli Serdang. The data collection process was carried out by means of interviews with several traders selling around the Tanjung Morawa Market area and documentation then carried out a qualitative descriptive research method approach. The results of this study show that there is a significant impact of the covid19 pandemic on UMKM.